A training programme for medical students in providing spiritual care to people with advanced diseases and their loved ones: A case study from the Collegium Medicum in Bydgoszcz, Nicolaus Copernicus University in Toruń, Poland - Fopka-Kowalczyk, Małgorzata; Groves, Richard; Larkin, Philip; Krajnik, Małgorzata (Frontiers in Cardiovascular Medicine, 2022)
Purpose: This article presents the first programme on spiritual care particularly for people with advanced life-limiting illness including heart failure, lung disease or cancer for medical students in Poland implemented at the Collegium Medicum in Bydgoszcz of the Nicolaus Copernicus University in Toruń. Methods and materials: Several steps were identified for the development of the programme, including: preliminary work on the content of the programme, agreement on key concepts, terms, and definitions; consultations with coaches and teachers of spirituality in medicine from international centres; analysis of the available international research and publications on teaching spirituality; development of the first programme on spirituality for medical students, and its implementation at the Collegium Medicum in Bydgoszcz. Results: A step by step approach resulted in the introduction of first Polish spiritual curriculum for medical students. The spirituality curriculum will contribute to better care for the people with advanced illness such as heart failure, chronic lung disease or cancer and improve the quality of relationships between professionals and patients. Conclusion: The article presents the content of the program, the expected learning objectives and ascribed teaching methods, along with the preliminary evaluation made by students.